Innovating undergraduate pathology education through public engagement. - Mukundu Nagesh, Navin; Chiva Giurca, Bogdan; Lishman, Suzy (Virchows Archiv: European Journal of Pathology, 2018)
The trends in modern undergraduate medical education focus on a patient-centred approach through problem-based learning over the traditional modular curriculum. Integrating pathology into this style of learning has resulted in the dilution of core scientific principles which may have contributed to reduced understanding and interest in the subject. We aim to innovate pathology education by utilising National Pathology Week which is organised by the Royal College of Pathologists to develop the public engagement model which empowers students to learn pathology by teaching the public. Through this model, we hope to generate a greater interest in pathology at both undergraduate and postgraduate stages of education. We obtained funding from the Royal College of Pathologists to organise National Pathology Week at Exeter Medical School and the Royal Devon & Exeter Hospital. We involved 125 undergraduate student volunteers from health-related courses. We designed a curriculum aiming to educate both students and public on current topics such as cancer screening programmes, antibiotic resistance, diagnosis of inflammatory bowel disease and the role of pathologists. We hosted 15 pathologists, biomedical scientists and microbiologists to engage with students, share experiences and offer an insight into their careers. Through this project, we interacted with over 500 members of the public and 150 school students. The medical student volunteers developed a range of skills including competent use of microscopes to visualise pathology slides, effective communication with lay audiences to teach pathology and understanding of the clinical application of pathology. We believe the public engagement model of teaching undergraduate students has the potential to develop a greater interest in pathology whilst benefitting the wider community.